Nasty wars and needy veterans? How cognitive polyphasia may explain conceptualizations of the U.S. Iraq and Afghanistan veterans as victims and heroes - Phillips, Rita Helena (Frontiers in Sociology, 2024)
Representative opinion polls indicate that members of the U.S. public may hold dichotomous perceptions of their veterans. While the majority of the U.S. public appreciates and honors their veterans, they are also considered to suffer from war-induced trauma and physical disabilities. Victimizing attitudes toward the veteran population may result in stigmatization and a more difficult transition into civilian society. This may be particularly problematic for U.S. veterans who were deployed to Iraq and Afghanistan as this younger veteran population needs to reintegrate not only into civilian society but also into civilian workplace settings. The present study aims to uncover and unravel underlying rationalities that justify heroizing and victimizing sentiments in relation to Iraq and Afghanistan veterans. In order to delve beyond socially desirable reporting and cultural norms, in-depth semi-structured interviews with 29 individuals (20 non-veterans and 9 veterans) were conducted. Three themes were identified by thematic analysis: Theme 1 “Individual Understandings of the Deployments to Iraq and Afghanistan” represents an underlying framework that tainted perceptions of Theme 2 “Conceptualizations of war, deployment, and violence” and Theme 3 “Evaluations of the veteran’s personality.” If the deployments were considered justified, then veterans were heroized, characterized with supreme altruistic traits when compared with civilians. Negative effects on health that were arbitrarily related to deployment experience were classified as short-lived. If the deployments were scrutinized, then veterans were considered as naïve victims of a deceitful government, suffering from long-term health problems. Importantly, as discussions surrounding the legitimacy of the deployments were context-dependent, the participants were able to hold perceptions of veterans as victims and as heroes side by side. In conclusion, the heroization and victimization of veterans may be the result of considering different viewpoints, elucidating diversity and access to equivocal information in an increasingly complex social world. Although the present findings may require further validation, they suggest that changing negative, stereotyping perceptions of veterans may require a coherent rationale for deployments and uniform mission objectives.